2013
DOI: 10.1080/19371918.2013.774666
|View full text |Cite
|
Sign up to set email alerts
|

Brief Strategic Family Therapy: Engaging Drug Using/Problem Behavior Adolescents and Their Families in Treatment

Abstract: Despite the efficacy of family-based interventions for improving outcomes for adolescent behavior problems such as substance use, engaging and retaining whole families in treatment is one of the greatest challenges therapists confront. This article illustrates how the Brief Strategic Family Therapy® (BSFT®) model, a family-based, empirically validated intervention designed to treat children and adolescents’ problem behaviors, can be used to increase engagement, improve retention, and bring about positive outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…In addition, physicians can enlist active caregiver collaboration in supporting treatment enrollment, offering not only to provide a program referral but also to facilitate the initial contact between the family and SU treatment providers. Strength-based strategies such as these are consistent with established family-based treatment engagement procedures for ASU and associated problems (e.g., Alexander, Waldron, Robbins, & Neeb, 2013; Liddle, 2002; Szapocznik, Zarate, Duff, & Muir, 2013). Likewise, these physician-caregiver adaptations to RT are consistent with empirically validated family-based clinical procedures that mobilize caregiver support to influence highly resistant adolescents to enroll in SU treatment (Kirby et al, 2015; Waldron, Kern-Jones, Turner, Petersen, & Ozechowski, 2007).…”
Section: Referral To Treatmentmentioning
confidence: 67%
“…In addition, physicians can enlist active caregiver collaboration in supporting treatment enrollment, offering not only to provide a program referral but also to facilitate the initial contact between the family and SU treatment providers. Strength-based strategies such as these are consistent with established family-based treatment engagement procedures for ASU and associated problems (e.g., Alexander, Waldron, Robbins, & Neeb, 2013; Liddle, 2002; Szapocznik, Zarate, Duff, & Muir, 2013). Likewise, these physician-caregiver adaptations to RT are consistent with empirically validated family-based clinical procedures that mobilize caregiver support to influence highly resistant adolescents to enroll in SU treatment (Kirby et al, 2015; Waldron, Kern-Jones, Turner, Petersen, & Ozechowski, 2007).…”
Section: Referral To Treatmentmentioning
confidence: 67%
“…Therefore, the level of attrition (or participant dropout) is also of concern in intervention studies. Szapocznik et al (2013) state that having families engaged throughout the treatment process enhances participation and so positive outcomes for those undergoing treatment. Thompson, Bender, Windsor, and Flynn (2009) found that having participants' homes as a setting for the intervention increased participation and engagement.…”
Section: Engaging the Familymentioning
confidence: 99%
“…Many studies merely used case examples to illustrate their interventions (Bickerton, Hense, Benstock, Ward, & Wallace, 2007;Dausch & Saliman, 2009;Lepage, 2005;Marvel et al, 2009;Philipp, 2012;Smith & Handler, 2009;Szapocznik, Zarate, Duff, & Muir, 2013;Williamson et al, 2014). Therefore, the level of attrition (or participant dropout) is also of concern in intervention studies.…”
Section: Engaging the Familymentioning
confidence: 99%
“…Many studies and reports document adverse effects of substance use disorders (SUDs) on the family system and individual members, including children [18]. These disorders clearly affect many people in addition to the individual with the problem, often creating a burden for the family and its members.…”
Section: Effects Of Substance Use Disorders On the Familymentioning
confidence: 99%
“…Outreach efforts may be needed to engage families in treatment. A number of effective interventions have been used with families to increase their rates of involvement with the family member with the SUD in treatment [8, 9, 22]. …”
Section: Interventions For Social or Family Problemsmentioning
confidence: 99%